Socioeconomic evaluation of agroforestry systems (Case study: Northern Iran) - M. Mohebi Bijarpas; T. Rostami Shahraji; S. Mohammadi Limaei (Journal of Forest Science, 2015)
The aim of this research was to investigate the socioeconomic values of different land use in the agroforestry system. Questionnaires were used to collect social and economic data in two villages at Guilan province, northern Iran. Internal Rate of Return (IRR) and Profitability Index (PI) were used for cost-benefit analysis. Net Present Value (NPV) of different farming systems was determined. ANOVA test was used to compare the outcomes of different land use. The results indicated that there is a significant relationship between literacy and variety of land use in two villages. Results of IRR and PI indices show that these indices were higher in poplar plantation than in the other land use (paddy and tea field, horticulture and vegetable). Results of ANOVA test showed that there is a significant difference between net incomes from different farming systems in Tamchal village. Furthermore, the ANOVA test showed that there is no significant difference between net incomes from different farming systems in Narenj Bon Paeen village. The results showed that farmers tend to participate in training and promoting classes associated with the maximum use of land. Chi-squared test was used in order to determine the effect of participation in training and promoting classes on multiple uses of land, land use change, sericulture, and apiculture. The results of Chi-squared test showed that there is a significant and positive relationship between people's participation rates and the multiple use of land. In overall, results showed that traditional agroforestry systems provide a higher income than monoculture in the study area.